Let f(x) = (cos(x))^(1/x^2)
We are looking for lim x -> 0 f(x)
ln(lim x -> 0 f(x)) = lim x -> 0 ln f(x)
= lim x -> 0 ln (cos(x))^(1/x^2)
= lim x -> 0 (1/x^2) * ln (cos x) //exponential rule for logarithms
= lim x -> 0 (ln(cos x))/(x^2)
= lim x -> 0 ((1 / cos x) * (-sin x)) / (2x) //L'Hopital's rule, as the previous form is a 0/0 form
= lim x -> 0 (-tan x) / 2x //tan = sin / cos
= lim x -> 0 (-sec^2 x) / 2 //L'Hopital's rule again, 0/0
= -1/2 //you can substitute now, as it is no longer 0/0
Thus, lim x -> 0 f(x) = exp(ln(lim x -> 0 f(x))) = exp(-1/2)